2017
DOI: 10.5152/dir.2017.16364
|View full text |Cite
|
Sign up to set email alerts
|

Shining light in a dark landscape: MRI evaluation of unusual localization of endometriosis

Abstract: Endometriosis is a systemic disease that affects about 10% to 20% of women during their reproductive age, characterized by the presence of endometrial glands and stroma outside the uterine cavity (1). Endometriosis lesions are characterized by intralesional recurrent bleeding during menses, because of the hormonal responsiveness of ectopic endometrial tissue, with resulting fibrosis. Typical symptoms are cyclic or chronic pelvic pain, dysmenorrhea, dyspareunia, and pain during defecation or urinating. Unusual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…Several studies reported that MRI evaluation is highly accurate for preoperative surgical planning [ 10 ], in accordance with the European Society of Urogenital Radiology’s (ESUR) guidelines 2017 [ 6 ]; in fact many large centers utilize these studies routinely, especially in the case of equivocal recto–vaginal, ureteral, or bladder endometriosis [ 18 , 19 , 20 ]. It follows that MRI is assuming an increasingly central role in the pre-operative diagnosis of endometriotic disease [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies reported that MRI evaluation is highly accurate for preoperative surgical planning [ 10 ], in accordance with the European Society of Urogenital Radiology’s (ESUR) guidelines 2017 [ 6 ]; in fact many large centers utilize these studies routinely, especially in the case of equivocal recto–vaginal, ureteral, or bladder endometriosis [ 18 , 19 , 20 ]. It follows that MRI is assuming an increasingly central role in the pre-operative diagnosis of endometriotic disease [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 98%
“…The posterosuperior diaphragm is the most common location for the diaphragmatic implants because endometrial cells travel through the paracolic gutter and implant on the right hemidiaphragm [21]. In contrast, the presence of phrenocolic and falciform ligaments prevent the endometrial cells from coming into contact with the left hemi-diaphragm [22].…”
Section: Radiologic Studiesmentioning
confidence: 99%
“…Other rare extraperitoneal localizations include pelvic nerve implants, diaphragmatic, pleural and chest involvement. 48 Tips and tricks…”
Section: Imagingmentioning
confidence: 99%